2011
DOI: 10.1007/s00106-011-2321-0
|View full text |Cite
|
Sign up to set email alerts
|

Audiologische Ergebnisse mit Cochlear implant bei einseitiger Taubheit

Abstract: These preliminary results confirm the effectiveness of CI treatment in unilateral deafness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(31 citation statements)
references
References 24 publications
4
19
0
6
Order By: Relevance
“…The observed effects on tinnitus after completing the standard CI rehabilitation phase are in line with previous studies Kleinjung et al, 2009;Arndt et al, 2010;Buechner et al, 2010;Palau et al, 2010;Jacob et al, 2011;Kleine Punte et al, 2011;Firszt et al, 2012b;Ramos et al, 2012;Hansen et al, 2013;Távora-Vieira et al, 2013]. Our results show a decrease in tinnitus perception over the approximately 8 weeks of CI rehabilitation that is not caused by the surgery itself, which is consistent with an earlier case report [Gartrell et al, 2014].…”
Section: Standard CI Rehabilitationsupporting
confidence: 82%
See 1 more Smart Citation
“…The observed effects on tinnitus after completing the standard CI rehabilitation phase are in line with previous studies Kleinjung et al, 2009;Arndt et al, 2010;Buechner et al, 2010;Palau et al, 2010;Jacob et al, 2011;Kleine Punte et al, 2011;Firszt et al, 2012b;Ramos et al, 2012;Hansen et al, 2013;Távora-Vieira et al, 2013]. Our results show a decrease in tinnitus perception over the approximately 8 weeks of CI rehabilitation that is not caused by the surgery itself, which is consistent with an earlier case report [Gartrell et al, 2014].…”
Section: Standard CI Rehabilitationsupporting
confidence: 82%
“…Nevertheless, tinnitus can also be a complication after cochlear implantation [Di Nardo et al, 2007;Postelmans et al, 2007;Hou et al, 2010], possibly related to cochlear damage due to the surgery [Nordfalk et al, 2014;Todt et al, 2014]. Van de Heyning et al [2008] reported the first results of cochlear implantation in an attempt to treat tinnitus in single-sided deafness (SSD), after which many studies followed on tinnitus suppression in SSD [Kleinjung et al, 2009;Arndt et al, 2010;Buechner et al, 2010;Palau et al, 2010;Jacob et al, 2011;Kleine Punte et al, 2011;Firszt et al, 2012b;Mendes et al, 2012;Ramos et al, 2012;Hansen et al, 2013;Távora-Vieira et al, 2013 and reviewed by Arts et al, 2012;Blasco and Redleaf, 2014;Tokita et al, 2014;Vlastarakos et al, 2014;van Zon et al, 2015]. As a common conclusion it can be stated that cochlear implantation is a viable treatment option for tinnitus in SSD.…”
Section: Introductionmentioning
confidence: 99%
“…Although a contralateral routing of the signal (CROS) may be beneficial in some situations, it does not restore hearing to the poor ear and, in some cases, has been detrimental [Hol et al 2004; Hol et al 2010; Wazen et al 2005]. Cochlear implantation as a treatment for adults with UHL is on the rise [Arndt et al 2011; Buechner et al 2010; Firszt et al 2012; Jacob et al 2011; Ramos et al 2012], yet little is known about factors that could impact performance or whether there is a group at risk for poor outcomes when hearing is near-normal in one ear. Likewise in children with UHL, predictive variables for cochlear implant success are unknown, and whether these factors change developmentally has not been determined.…”
Section: Discussionmentioning
confidence: 99%
“…Patients in the cohort exhibited improvement in sound localization as well as a subjective sense of greater ease in listening in noisy environments. He further noted that placing a CI did not have any impact on the normal hearing side 30 .…”
Section: Effectiveness Of Cis To Improve Sound Localization and Speecmentioning
confidence: 99%